Leveraging Data Analytics to Optimize Marketing Strategies for Retaining Loyal Customers in Czech Restaurants - Kosturiakova, Zuzana; Machek, Martin; Nízký, Jan; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This thesis explores how transactional data analytics can optimise customer loyalty strategies within the hospitality industry. Despite widespread adoption of loyalty programs, many operators underutilise their behavioural and purchase data, limiting their ability to retain and engage high-value guests. Using the CRISP-DM framework, this study analyses a one-year dataset from an anonymised Prague-based restaurant chain, focusing on visit frequency, spending patterns, and transaction history. RFM segmentation combined with K-means clustering uncovered distinct customer groups and behavioural patterns, which were mapped against Oliver’s psychological loyalty development model (cognitive, affective, conative, action). A Random Forest churn prediction model further identified customers at risk of disengagement. Additionally, a managerial interview provided qualitative insights to contextualise the findings and evaluate the practical application of data-driven loyalty strategies within a traditional hospitality culture. Based on the results, recommendations include introducing a structured tier-based loyalty approach, implementing light-touch behavioural incentives, and establishing a Loyalty Intelligence System to leverage real-time dashboards for customer behaviour monitoring and programme performance evaluation. This research provides actionable insights for hospitality operators seeking to balance personal, customer-centric service with data analytics to drive sustainable customer relationship and revenue growth.
Vedoucí práce: Martin Machek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses